PEMBERDAYAAN INDUSTRI KECIL DAN MENENGAH DALAM PASAR UNTUK MENGATASI PENCARI KERJA DI KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR TAHUN 2014 - Fitrahadi Khaz; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Looking at the data distribution of the population, the District of Bagan Sinembah is a region with the highest population density is ± 163.02 inhabitants /km2. The population is too big and is not comparable with the availability of jobs will cause a portion of the population who are at working age do not get a job. In Sub Chart Sinembah main source of income, the majority of the population is mostly of farm incomes and growing industrial large-scale palm oil processing. Subdistrict Chart Sinembah small and medium industries have the largest network in Rokan Hilir. Empowerment of small and medium industries are potentially in overcoming job seekers in the district of Rokan Hilir Chart Sinembah 2014.Based on the results of this study concluded that the empowerment and the development potential of small and medium industries in the District Bagan Sinembah more focused on industrial activity based on democratic economy, advanced, competitive, and independent and contribute positively to the economic life of the people in the industrial sector and trade. One objective of the empowerment of small and medium industries are the insistence on the SME entrepreneurs are able to expand the economic base and provide significant contributions in expanding employment opportunities, namely by increasing the region's economy and economic security districts.Keywords: Empowerment of Small and Medium Industry, Labor